Exposition of Measure Risk within Quality Norms by Solving the Problems of the Persons and Property Patronage - Marian Mesaros (Communications - Scientific letters of the University of Zilina, 2002)
Qualitative norms at present being introduced into all sectors of management also enter successfully new sorts of managerial activities including safety management. Contractual safety interest of personal, material and non-material protected assets by means of a model process orientated protection meets fully requirements of continual improvements of managerial quality system of protection process.The aim of the article is to arrange logically the phases of the safety process development by means of accentuating existence of the private security service law, categorisation of individual parts of the hierarchy of the development of security services and subsequent detection and pre-estimating risks in the framework of the safety system as a basic element of the safety conception.